BLOCKCHAIN-BASED INTER-ORGANIZATIONAL INFORMATION SHARING WITH CONFIDENTIALITY PROTECTION: A SYSTEMATIC LITERATURE REVIEW - Kadis, Mohd Rizal; Azzuhri, Saaidal Razalli; Kiah, Miss Laiha Mat; Herawan, Tutut (Malaysian Journal of Computer Science, 2024)
Blockchain technology has emerged as a transformative solution for inter-organizational information sharing, offering enhanced security and transparency. Transparency aims to build trust, ensure data integrity, guarantee accountability, and prevent unfair practices. However, this presents a dilemma for organizations prioritizing confidentiality, making the full implementation of blockchain challenging. To address these concerns, numerous studies have explored methods for preserving confidentiality and privacy within blockchain systems. Recent research has conducted systematic reviews focusing on security and user-centric approaches to data privacy in blockchain. In this paper, we present a systematic literature review to examine techniques proposed for preserving confidentiality in inter-organizational information sharing. In total, 51 study papers were selected for synthesis. The results indicate the techniques can be categorized into seven groups: privacy-preserving, authorization, data perturbation, symmetric encryption, asymmetric encryption, isolated area, and comprehensive tool. We identified that these techniques are applicable to 11 scenarios, as outlined in this paper.